Robust adaptive path following for a nonlinear third order Nomoto's ship model - Taktak-Meziou, M; Ghommam, J; Derbel, N (2010 7th International Multi-Conference on Systems, Signals and Devices, 2010)
In this paper, an adaptive backstepping method is used for a ship course tracking control. This has been done by applying a reference signal derived from a LOS algorithm. The ship model is described by a third order nonlinear model whose parameters are unknown. The control design uses estimate values of the unknown parameters of the system. Then, adaptive laws of the estimation of these values have been proposed. The stability of the controlled system has been ensured by the use of a Lyapunov function. Simulation results show the effectiveness of the proposed approach and the designed controller can be used to the ship course tracking with good performances.